2015
DOI: 10.2147/ndt.s79586
|View full text |Cite
|
Sign up to set email alerts
|

Early stages of pediatric bipolar disorder: retrospective analysis of a Czech inpatient sample

Abstract: BackgroundApproximately 30%–60% of adults diagnosed with bipolar disorder (BD) report onset between the ages 15 and 19 years; however, a correct diagnosis is often delayed by several years. Therefore, investigations of the early features of BD are important for adequately understanding the prodromal stages of the illness.MethodsA complete review of the medical records of 46 children and adolescents who were hospitalized for BD at two psychiatric teaching centers in Prague, Czech Republic was performed. Frequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
1
11

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 45 publications
1
10
1
11
Order By: Relevance
“…Rates for the 10 to 14 years age group were 134 (USA), 3.9 (Australia), 1.3 (New Zealand), 0.48 (England) and 0.46 (Germany). Similar low rates for inpatient diagnoses were found in the Czech Republic (Goetz et al, 2015) and for both inpatient and outpatient children and youth in Denmark (Kessing, Vradi, & Andersen, 2014). These recent studies of diagnosis rates in Europe and Australasia show little to no deviation from older British, European and Australasian studies that found mania/hypomania/bipolar disorder to be rare in adolescence and exceedingly rare or not detected in prepubertal children (Barton-Hall, 1952; Räsänen, Tiihonen, & Hakko, 1998; Sigurdsson, Fombonne, Kapil, & Checkley, 1999; Sourander, 2004; Thomsen, Moller, Dehlholm, & Brask, 1992; Werry & McClellan, 1992).…”
Section: Introductionsupporting
confidence: 69%
See 1 more Smart Citation
“…Rates for the 10 to 14 years age group were 134 (USA), 3.9 (Australia), 1.3 (New Zealand), 0.48 (England) and 0.46 (Germany). Similar low rates for inpatient diagnoses were found in the Czech Republic (Goetz et al, 2015) and for both inpatient and outpatient children and youth in Denmark (Kessing, Vradi, & Andersen, 2014). These recent studies of diagnosis rates in Europe and Australasia show little to no deviation from older British, European and Australasian studies that found mania/hypomania/bipolar disorder to be rare in adolescence and exceedingly rare or not detected in prepubertal children (Barton-Hall, 1952; Räsänen, Tiihonen, & Hakko, 1998; Sigurdsson, Fombonne, Kapil, & Checkley, 1999; Sourander, 2004; Thomsen, Moller, Dehlholm, & Brask, 1992; Werry & McClellan, 1992).…”
Section: Introductionsupporting
confidence: 69%
“…The influence of the traditional perspective on BD among academics in non-US countries may also be reflected in clinical practice with hospital discharge diagnosis rates for BD in the paediatric age range. Rates were found to be orders of magnitude lower in other nations compared to the United States (Clacey et al, 2015; Goetz et al, 2015; Kessing et al, 2014). This influence may also account for scepticism of PBD in surveys among child and adolescent psychiatrists in Germany (Meyer, Koßmann-Böhm, & Schlottke, 2004), Australia and New Zealand (Parry, Furber, & Allison, 2009), and the previously mentioned clinical vignette studies showing British child and adolescent psychiatrists having more conservative diagnostic practices compared to their US counterparts (Dubicka et al, 2008).…”
Section: Discussionmentioning
confidence: 92%
“…28,29 Several studies have recognized mood lability, major depressive episodes, subsyndromal manic symptoms, a diagnosis of a bipolar spectrum disorder (such as cyclothymia or BD not otherwise specified), and mood-congruent psychotic symptoms as precursors of BD. [30][31][32] On the other hand, in clinical practice, identification of a symptomatic high-risk BD phase is complicated by the complex nature of dimensions of this disorder, by potentially different symptom presentations in children and adolescents, 5,21,33 and by the blurred lines between the prodrome and the disease itself. 34 Retrospective and prospective studies have revealed a pattern of putative prodromal symptoms, of which mood lability/mood swings/cyclothymic features, depressive mood, racing thoughts, irritability, and physical agitation are most commonly reported.…”
Section: Clinical Presentation Of Early Stagesmentioning
confidence: 99%
“…In contrast, apart from a small number of academic units in other countries (Parry et al 2019b), the classical view held sway internationally. This was re ected in inpatient discharge diagnosis rates where the US had several-hundred-fold higher rates of BD diagnosis than in England, Australia, New Zealand, Germany, Czech Republic, Denmark and Finland (Clacey et al 2015;Goetz et al 2015;Kessing et al 2014;Sourander 2004). It is also re ected in six longitudinal highrisk offspring of parents with BD studies, where only the Pittsburgh study that employs the PBD hypothesis found "50% had mania prior to age 12 (compared to 0% in other studies)" (Duffy et al 2017).…”
Section: Introductionmentioning
confidence: 97%